Investigating the Predictive Value of Lipoprotein(a) for Atherosclerotic Plaque Burden in Stable Angina Patients: A Mechanistic and Imaging-Based Study - Muhammad Ahmad Raza Butt, Muhammad Hammad Akhtar, Muhammad Irfan Akhtar, Ali Jarar Shah, Beenish Javaid, Muhammad Zarrar Arif Butt, Mohamad Khir Bin Johari, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Carotid intima-media thickness (CIMT) and plaque burden via ultrasound provide validatedmarkers of subclinical atherosclerosis.